Ekstremisme dan Solusi Moderasi Beragama di Masa Pandemi Covid 19 - Bibi Suprianto (Jurnal Studi Agama, 2022)
Extremism has been a hot issue for years around the world. Until now, many scientists have investigated extremism through various aspects and their knowledge. however, only a few researchers have investigated the mechanisms of extremism and solutions for religious moderation during the Covid-19 pandemic. The purpose of this study is to examine how the solution to extremism in religious moderation is during the covid-19 pandemic. This research is aqualitative research which is literature review. The author uses data analysis methods such as data reduction, data presentation and drawing conclusions. The results of this study indicate that extremism and solutions to religious moderation during the covid-19 pandemic are as follows; 1) extremism can be prevented through national insight during a pandemic to understand religious divisions; 2) Religious extremism can be tolerated during a pandemic in order to provide space for awareness of religious diversity; 3) not being extreme towards one's own religion; 4) Extremism can be carried out in a friendly manner with local culture during a pandemic. The researcher's findings show that extremism and the solution to religious moderation during the COVID-19 pandemic can be done by developing various social aspects